The Effects of Brand Trust, Perceived Quality and Halal Knowledge on Richeese Factory Consumers’ Purchase Intention - Misliani; Indah Permatasari Siregar; Damri Batubara (Riset Anak Bangsa, 2026)
This study was motivated by fluctuations in consumer purchase intention at Richeese Factory Padangsidimpuan, where interest declined three months after the outlet's grand opening, recovered in subsequent months, and then decreased again. The study analyzes the effects of brand trust, perceived quality, and halal knowledge on consumers' purchase intention toward Richeese Factory in Padangsidimpuan City. A quantitative design was employed with 97 respondents selected through convenience sampling using the Lemeshow formula. Data were collected through questionnaires and documentation and analyzed using validity and reliability tests, classical assumption tests, multiple linear regression, partial t-tests, the simultaneous F-test, and the coefficient of determination in SPSS version 23. The findings show that brand trust and halal knowledge significantly affect purchase intention, whereas perceived quality does not. These results identify brand trust and halal knowledge as important determinants of consumer purchase intention. Future studies should examine additional variables and different samples to obtain more comprehensive evidence.